0363 Occupational exposure to high frequency electromagnetic fields and risk of brain tumours in the interocc study. (21st August 2017) - Vila, Javier; Turner, Michelle C; Gracia-Lavedan, Esther; Figuerola, Jordi; Bowman, Joseph D; Kincl, Laurel; Richardson, Lesley; Benke, Geza; Fleming, Sarah; Hours, Martine; Krewski, Daniel; McLean, Dave; et al.
Abstract : Introduction: The International Agency for Research on Cancer classified radiofrequency (RF) electromagnetic fields (EMF) as possibly carcinogenic based on limited evidence in human studies of cell phone use and in animal experiments, while occupational evidence was found inadequate due in part to limitations in exposure assessment. This study assesses possible associations between occupational exposure to RF or intermediate frequency (IF) EMF in INTEROCC participants using novel exposure assessment methodologies. Methods: A plausible index of cumulative exposure to RF and IF EMF was calculated using a source-exposure matrix and detailed interviews on work with or nearby EMF sources, both overall and in specific exposure time windows. Conditional logistic regression was used to investigate associations with glioma and meningioma risk. Results: Only 10% (n=769) of participants (n=7, 330) were ever exposed to RF and 1% (n=44) to IF EMF sources. Overall, there was no positive association between exposure to RF or IF EMF and glioma or meningioma risk, and the majority of odds ratios (ORs) were <1.0. Some elevated ORs were observed in the highest exposure quantile (90 th ) for both RF electric fields and IF magnetic fields in the 1–4 year exposure time window for glioma, but were not statistically significant. Conclusions: Lifetime occupational RF and IF exposures based on our index were not associated with the risk of glioma or meningioma. Further work should include more exposed participants and examine alternative exposure or dose indices such as those incorporating thresholds on biological effects or combinations of static and RF magnetic fields.